Alison M. Garnham, Hans Keller and Internment: The Development of an Emigré Musician 1938-48 (2011) - Cox, Gareth (Journal of the Society for Musicology in Ireland, 2012)
A review of Alison M. Garnham, Hans Keller and Internment: The Development of an Emigré Musician 1938-48 (London: Plumbago, 2011). ISBN 978-0-9556097-7-3.